Agrarian anti-reform, reform and counter-reform public policies for agriculture in peru, years 1950-2016. A shade look - Sueiro Cabredo, Ernesto (2020)
This paper aims at describing and analyzing the public policies adopted on anti-reform, reform and counter-reform in Peru from 1950 to 2016. To this end, all the agrarian policies followed and implemented by each government included in this period of time have been reviewed. Moreover, personal testimonies of key moments are used to contribute to the analysis of the facts. The process allowed to get aware of the conditions that led to the need of an Agrarian Reform in Peru, which meant changes for both landowners and medium and small farmers and peasants, during the Juan Velasco Alvarado government. Subsequently, the government of Francisco Morales Bermudez started the agrarian counter-reform, which undid the Velasco Reform to favor the market of private lands. Furthermore, this system was consolidated during the neoliberal government of Alberto Fujimori that is maintained until today.